Assessing the impact of employee participation on team-work performance: A way to reinforce entrepreneurship - Aikaterina Oikonomou (SPOUDAI - Journal of Economics and Business, 2018)
The purpose of this study is to examine how the promotion of active participation and teamwork within the firm contribute to business success and consequently helps firms to gain a competitive advantage. Initially, the emphasis is placed on employee participation approach, its characteristics and its contribution to continuous improvement. The concept of teamwork and its basic characteristics are also analyzed for entrepreneurship reinforcement. Specifically, we argue that business units need to adjust their strategy and pursue strategic management practices, in order to exploit the beneficial potentials of employee involvement. In such a way they may achieve a sustainable competitive advantage. The findings of this study are useful to top and middle level managers and policy makers.
Keywords: L1; L26; J21; 330; Employee Participation; Team Work Performance; Entrepreneurship; Strategic Management; Competitive Advantage